Research in economic history. Vol. 37 - Hanes, Christopher (Emerald Publishing Limited, 2021)
In this 37th volume of Research in Economic History, editors Christopher Hanes and Susan Wolcott assemble a group of lead experts to showcase new historical data, analyses of historical questions, and an investigation of historians' networks. The volume covers a wide range of ideas, beginning with an examination of the sharp decline in school attendance among white children in the Southern US after the Civil War, followed by a study on the fiscal administration of an experimental parliamentary subsidy on English knight's fees and income from 1431. A third paper assembles new county-level, household-level, and individual-level data, including new complete-count IPUMS microdata databases of the 1830-1880 censuses, to evaluate different theories for the nineteenth-century American fertility decline. The volume then pivots to deal with the development of banking in the Crown of Aragon from the end of the 13th century through the establishment of money changers. Finally, the volume summarizes in detail the content of Pieter Stadnitski's revolutionary 1787 report An Explanatory Message Concerning the Funds, analyzing its arguments with the context of Dutch archival materials including deeds, newspaper reports, and letters, as well as congressional records from American sources. This new volume presents fascinating new areas of enquiry and analysis for all scholars in the field of economic history, including economists, historians and demographers.
Keywords: Economic history.; Business & Economics -- Economic History.; elektronické knihy; electronic books